2008
DOI: 10.1080/14623940802005384
|View full text |Cite
|
Sign up to set email alerts
|

Holistic reflection in teacher education: issues and strategies

Abstract: Current practices in teacher education are standards-driven and place a great deal of emphases on micro-analyzing practices and reflecting on technical problems in teaching. Processes that are attributed to one's inner life, and that are associated with the artistic/aesthetic domains, such as, intuition, contemplation, visualization, and imagination are largely ignored in teacher education programs. Many educators, however, believe that the cultivation of the inner life, in particular, the imagination, is crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…In fact, teachers stated that their ability to reflect improved after joining the school mostly because of the school's vision as a learning community and its purposefully planned PD program. This is in line with what is documented in the literature: a holistic approach that goes beyond technical training needs to be adopted (York-Barr et al 2006, Klein 2008; and even experienced teachers would benefit from ongoing training to develop higher levels of reflective practice (Galvez-Martin 1997, Hammrich et al 1990). The teachers identified two main contextual factors that had an impact on developing their reflective practice at the school.…”
Section: Discussion: Opportunities and Barrierssupporting
confidence: 56%
See 4 more Smart Citations
“…In fact, teachers stated that their ability to reflect improved after joining the school mostly because of the school's vision as a learning community and its purposefully planned PD program. This is in line with what is documented in the literature: a holistic approach that goes beyond technical training needs to be adopted (York-Barr et al 2006, Klein 2008; and even experienced teachers would benefit from ongoing training to develop higher levels of reflective practice (Galvez-Martin 1997, Hammrich et al 1990). The teachers identified two main contextual factors that had an impact on developing their reflective practice at the school.…”
Section: Discussion: Opportunities and Barrierssupporting
confidence: 56%
“…Tools and methods to develop reflective practice Some educators view reflective practice as a process that can be developed using tools such as diaries (Heath 1998), action learning groups (Williamson 1997), autobiographical stories (Brookfield 1995), sketching (Willis 1999), case studies (Sparks-Langer et al 1990, Lundberg andLevin 2003), mentoring (Drago-Severson 2004), portfolios (Dietz 1999), medicine wheel (Klein 2008), community of practice (Ng and Tan 2009) and action research (Calhoun 2002). Despite the increased interest in promoting reflective practice, research has found that the impact of these attempts on the ability of teachers to reflect at high levels is questionable.…”
Section: Definition and Levels Of Reflectionmentioning
confidence: 99%
See 3 more Smart Citations